Relationship between splenic size and splenic function. Issue 1 (January 1978) - Smart, R C; Ryan, F P; Holdworth, C D; Preston, F E
Abstract : The rate of clearance of 51Cr labelled heat-damaged red cells from the circulation has been compared with the dimensions of the posterior scan of the spleen in 79 cases including nine controls. A strong negative correlation was found between the clearance half-time and the parameters of the scan but, as there was a large variation about the regression line, in the assessment of hyposplenism determination of the rate of clearance of heat-damaged red cells cannot be replaced by the easier determination of spleen size by scanning.